International Knowledge Spillovers: The Benefits from Employing Immigrants - Sanne Hiller; Jürgen Bitzer; Erkan Gören (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper explores the role of immigrant employees for a firm's capability to absorb international knowledge. Using matched employer-employee data from Denmark for the years 1999 to 2009, we are able to show that non-Danish employees from technological advanced countries contribute significantly to firm's economic output through their ability to access international knowledge. The empirical results suggest that the immigrants' impact increases if they come from technological advanced countries, have a high educational level, and are employed in high-skilled positions. However, the latter does not hold for immigrant managers.
Keywords: D20; J82; L20; 330